Advisor-student communication and the research process: Post-pandemic contests at the Graduate level - Barrales Martínez, Alfredo (HUMAN REVIEW. International Humanities Review / Revista Internacional de Humanidades, 2023)
Exploratory-descriptive study conducted in postgraduate studies of a public university in Mexico; objective: to identify Communication, socio-affective and technological nature obstacles, that during the pandemic became relevant in the research process for thesis. Method: quantitative with the use of questionnaire and structured interview. Inferences: socio-affective obstacles have an impact on the research process, especially in times of crisis; the relationship with the thesis advisor is a fundamental factor for continuity and permanence; technologies facilitate advisory-advised communication; the research process involved modifications and rethinking of research problems in virtual contexts.